SAT0351 Is Illness Perception and Coping Associated with the Patient-Related Treatment Delay in Early Rheumatoid Arthritis? An Explorative Study Within the Carera Trial. (9th June 2015) - Van der Elst, K.; De Cock, D.; Vecoven, E.; Arat, S.; Meyfroidt, S.; Joly, J.; Moons, P.; Verschueren, P.; Westhovens, R.
Abstract : Background: Persons, later on diagnosed with early rheumatoid arthritis (ERA), often delay their first contact with a health professional after symptom onset. Besides initial symptoms, psychosocial characteristics of individuals may influence their help-seeking behavior. Objectives: To explore the role of disease characteristics, illness perception and coping style on the patient-related delay at treatment initiation in recently diagnosed patients with ERA. Methods: This explorative, cross-sectional study included 112 patients with ERA from the CareRA trial of whom complete data on patient-related delay, coping and illness perception were available. In addition to baseline socio-demographic and clinical data, we collected information on the patients' psychosocial profile with the Utrecht Coping List and the Revised Illness Perception Questionnaire. Correlations were measured by Spearman's rho. By means of a regression analysis, we weighted the association of variables on patient-related delay. Results: The patient-related delay was positively correlated with perceptions of causality including psychological attributions (r=0.301, p=0.001), risk factors (r=0.189, p=0.045) and immunity (r=0.261, p=0.005), and with passive coping (r=0.222, p=0.018). It was negatively correlated with the 28-Swollen Joint Count (r=-0.194, p=0.040), perceptions of treatment control (r=-0.271, p=0.004) and illness coherence (r=-0.208, p=0.028). Clinical and psychosocial variables explained respectively 15% and 18% of the variability in patient-related delay. Conclusions: Aside from a lower swollen joint count, a longer patient-related delay was correlated with a passive coping style, a strong conviction of symptom causality, poor expected treatment control and a feeling of limited illness coherence. Psychosocial aspects could influence individuals' help-seeking behavior and are worthwhile to consider when aiming for a reduction of ERA treatment delay. Disclosure of Interest: None declared